Ghosts, Devil, God and Deities: Cohabitation in "Ongkarn Chaengnam" - Chanklin, Nawamon (RUSAMILAE JOURNAL, 2022)
Many scholars believe that “Ongkarn Chaengnam” is the oldest Thai literature of Ayutthaya as it appears in written literature. Considering the overall content, “Ongkarn Chaengnam” is considered to be a type of liturgical literature in the Si Satcha Pankan Royal Ritual or the Royal Ritual of the Holy Spirit. Most of the study about “Ongkarn Chaengnam” tried to understand its origin, language or how it be used in rituals. But this article will present “Ongkarn Chaengnam” on the issue of Cohabitation of Ghosts, Devil, God and Deities. Even they are different, but still being together without the myth of discrimination. It’s because, they have to do their own duties and functions.